Implementasi Strategi Dinas Perhubungan Kota Tangerang dalam Pengelolaan Angkot Si Benteng - Nuzullani, Isma; Arif Kurniawan, Irvan; Prasetyo, Eko (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
The Tangerang City Transportation Service has made a strategy to reduce congestion in Tangerang City, namely by improving the quality of public transportation services in Tangerang City, one of which is by having Sifort city transportation. The problems that occur in the implementation of Sifort's public transportation management are human resources, weak coordination and cooperation in the transportation sector, the system created to reduce traffic jams is less effective. The research method used is descriptive qualitative. The aim of the research is to find out the role of SiBenteng public transportation in reducing traffic jams in Tangerang City. There are still shortcomings in the implementation of the strategy created by the Tangerang city transportation department to reduce traffic jams with the presence of the Sibenteng public transportation, but in terms of the system used for payment, it already uses an information and communication technology system.